Discovery of physalin biosynthesis and structure modification of physalins in Physalis alkekengi L. var. Franchetii - Qu, Liyuan; Gan, Chunli; Cheng, Xiaoling; Lin, Congcong; Wang, Yanli; Wang, Libo; Huang, Jian; Wang, Jinhui (Frontiers in Plant Science, 2022)
Physalins, active ingredients from the Physalis alkekengi L. var. franchetii (P. alkekengi) plant, have shown anti-inflammatory, antioxidant and anticancer activities. Whereas the bioactivity of physalins have been confirmed, their biosynthetic pathways, and those of quite a few derivatives, remain unknown. In this paper, biosynthesis and structure modification-related genes of physalins were mined through transcriptomic and metabolomic profiling. Firstly, we rapidly and conveniently analyzed physalins by UPLC-Q-TOF-MS/MS utilizing mass accuracy, diagnostic fragment ions, and common neutral losses. In all, 58 different physalin metabolites were isolated from P. alkekengi calyxes and berries. In an analysis of the physalin biosynthesis pathway, we determined that withanolides and withaphysalins may represent a crucial intermediate between lanosterol and physalins. and those steps were decanted according to previous reports. Our results provide valuable information on the physalin metabolites and the candidate enzymes involved in the physalins biosynthesis pathways of P. alkekengi. In addition, we further analyzed differential metabolites collected from calyxes in the Jilin province (Daodi of P. alkekengi) and other provinces. Among them, 20 physalin metabolites may represent herb quality biomarkers for Daodi P. alkekengi, providing an essential role in directing the quality control index of P. alkekengi.